BOLAJAQ TEXNOLOGIYALÍQ TÁLIM OQÍTÍWShÍLARÍNA KIYIMDI KONSTRUKCIYALAWDÍ ÚYRETIW USÍLLARÍ - Berdimbetova, A.D. (SCIENCE and SOCIETY, 2025)
The article addresses the issues of effective teaching of clothing construction in the process of training future teachers of technological education. When designing and constructing clothing details, mainly models, graphics, SNIISHP, "EMKO SEV," and the Muller method were used. These methods play an important role in forming not only theoretical knowledge but also practical skills in students.